2016
DOI: 10.1111/dome.12082
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Social Change

Abstract: The growing impact of new media around the world has been the subject of study by scores of scientists in multidisciplinary fields. Satellite TV and the Internet have been viewed as instruments of social and political change — connecting communities, educating the youth, and creating social networks previously unaccounted for, like virtual groups. However, in the Arab World and the Middle East, such technological developments have been hailed as tools for the empowerment of marginalized communities such as wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 8 publications
0
20
0
6
Order By: Relevance
“…Although it is hard to measure such influence, it was evident that social networks became alternative platforms for news. As argued by various studies on the Tunisian uprisings (Castells, 2012;Chomiak, 2011;Karolak, 2018;Miladi, 2016;Zayani, 2015), thanks to these digital platforms, protesters managed to get their voices heard by and stories out to the world. Marginalized youth proved that they were not mere observers or followers of news but could become shapers of mainstream media's news agenda.…”
Section: Technology and Infrastructurementioning
confidence: 99%
See 1 more Smart Citation
“…Although it is hard to measure such influence, it was evident that social networks became alternative platforms for news. As argued by various studies on the Tunisian uprisings (Castells, 2012;Chomiak, 2011;Karolak, 2018;Miladi, 2016;Zayani, 2015), thanks to these digital platforms, protesters managed to get their voices heard by and stories out to the world. Marginalized youth proved that they were not mere observers or followers of news but could become shapers of mainstream media's news agenda.…”
Section: Technology and Infrastructurementioning
confidence: 99%
“…Thus, they not only monitored occurrences of possible corruption among candidates, but also checked media coverage against any possible ideological influences. At the same time, an analysis of the candidates' online activism during that election period revealed that contenders learned from the lessons of previous years and understood that social media was equally as important as traditional media, especially for reaching out to young voters (Miladi, 2016). Activities in the online sphere indicated that Facebook and Twitter had become battlegrounds for ideological fights, which the contestants and their supporters had to navigate skillfully.…”
Section: Technology and Infrastructurementioning
confidence: 99%
“…Beberapa penelitian menunjukan bagaimana kuatnya pengaruh Media sosial, komunikasi pembangunan, dan munculnya kelompok-kelompok berdaya (Pajar Hatma Indra Jaya) media sosial terhadap perubahan sosial di suatu masyarakat. Salah satu temuan yang paling fenomenal dari pengaruh media sosial ke masyarakat adalah kaitan antara media sosial dengan terjadinya revolusi politik di banyak negara kawasan Timur Tengah (the Arab Spring Countries' Revolutions) (Miladi, 2016). Penggunaan media sosial juga efektif dimanfaatkan untuk menyebarkan gagasan gerakan sosial mengkampanyekan program menyusui anak (Hartoyo & Supriadi, 2015).…”
Section: Gambar 1 Video Yang Menginspirasi Munculnya Pembangunan DI Gedongkiwounclassified
“…Despite or even because the repressive political systems, this critical public sphere slowly developed and culminated in street demonstrations. Considering the limited freedom of expression, the restrictive media policies and the systematic persecution of dissident media activists prior to the revolutionary movement in these countries [7], the upheavals represented a turning point in which new media have been extensively used as instruments of disagreement with the own political regimes. Nevertheless, transformation toward a critical public occurred earlier.…”
Section: The New Media and The Proliferation Of The Arab Springmentioning
confidence: 99%
“…The scientific landscape is also divided over the importance of social media during the Arab Spring. While some scholars extrapolate the role of the new media for anti-authoritarian movements [2,3,7,10], others try to take a more nuanced view, discouraging media determinism [1,5,8]. These uprisings neither have occurred due to increasing media consumption, nor have been influenced primarily by social media, but emerged mainly because of the enduring unfavorable social and economic conditions and the serious violations of human rights.…”
Section: The New Media and The Proliferation Of The Arab Springmentioning
confidence: 99%